Systematic Aggression Registration in Forensic Psychiatric Care: A Qualitative Study on Preconditions for Successful Implementation - Cappon, Leen (International journal of offender therapy and comparative criminology, 2024)
Available research emphasizes the importance of getting a systematic overview of inpatient aggression in forensic psychiatric care. However, the same research does not focus on how systematic aggression registration should be introduced in clinical practice. To facilitate the use of systematic aggression registration instruments, it is very relevant to gain insight into the perspective of staff members on the introduction of these instruments in daily clinical practice. Additionally, preconditions for achieving a successful implementation can be considered. Therefore, this study aims to gain insight into the perspective of the staff members on the implementation of a systematic aggression registration instrument—that is, the MOAS—in a forensic psychiatric unit. Interviews (n = 8) and a focus group with staff members were carried out. Three main themes: (1) creating the most appropriate context for introduction, (2) choice for the MOAS as relevant instrument, and (3) perpetuating the use of the MOAS in clinical practice are scrutinized. The mentioned preconditions can be used as guidelines when implementing systematic aggression registration in clinical practice. We hope that this paper can inspire other forensic psychiatric facilities to introduce systematic registration of aggressive incidents.